2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20190065
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical patterns and frequency of cutaneous manifestations in the elderly

Abstract: <p class="abstract"><strong>Background:</strong> Cutaneous manifestations are common in elderly. The elderly population is composed of persons over 60 years of age and very few studies are available on the dermatologic diseases in this group. This study was done to study the clinical pattern and frequency of cutaneous manifestations in the elderly.</p><p class="abstract"><strong>Methods:</strong> A cross sectional observational study was conducted on 540 patients, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…16 Grover et al observed loss of luster in 64%, vertical riding in 72.5%, and onychomycosis in 12%. 19 A study by Goyal et al showed that the most common six skin disorders were: xerosis (44%), diabetic dermopathy (36%), skin tags (32%), cutaneous infections (31%), and pruritis and seborrheic keratosis-30% each, respectively. 17 Xerosis accounted for the most common skin manifestation in our study, 50.1%.…”
Section: Resultsmentioning
confidence: 99%
“…16 Grover et al observed loss of luster in 64%, vertical riding in 72.5%, and onychomycosis in 12%. 19 A study by Goyal et al showed that the most common six skin disorders were: xerosis (44%), diabetic dermopathy (36%), skin tags (32%), cutaneous infections (31%), and pruritis and seborrheic keratosis-30% each, respectively. 17 Xerosis accounted for the most common skin manifestation in our study, 50.1%.…”
Section: Resultsmentioning
confidence: 99%